Assessment Synergistic Effects of Integrated Therapy with Epigallocatechin-3-Gallate (EGCG) & Arsenic Trioxide and Irradiation on Breast Cancer Cell Line - Vahid CHANGIZI; Samayeh AZARIASL; Elahe MOTEVASELI; Saeedeh JAFARI NODOOSHAN (Tehran University of Medical Sciences, 2020)
Background: Breast cancer is the most common invasive malignancy among women in the world. The current breast cancer therapies pose significant clinical challenges. Low-dose chemotherapy represents a new strategy to treat solid tumors in combination with natural products such as green tea catechins. Epigallocatechin-3-gallate (EGCG) is the major polyphenolic extract from green tea with potent anticancer and antioxidant effects. The purpose of this study was to investigate the effects of EGCG, Arsenic trioxide (ATO) and gamma radiation on MCF-7 cell line. Methods: The anti-proliferative effects of EGCG and ATO individually, moreover in combination with radiation on MCF-7 cells were evaluated with MTT assay. The expression of apoptotic gens (Bax, Bcl-2, Caspase-3 and Fas) was assessed by real-time PCR. Results: Based on the results of MTT assay, EGCG and ATO exhibited dose and time-dependent anti-proliferative effects on MCF-7 cells. The combined therapy of EGCG and ATO in presence and absence radiation could rise cell death up to 80%. Moreover, integrated therapy made Bax up-regulated and Bcl-2 down-regulated. Conclusion: In assessment synergistic effects of integrated therapy with EGCG and ATO and irradiation had been significant impact on low dose chemotherapy for breast cancer treatment.